Paroxysmal kinesigenic dyskinesia in a patient with a mutation and centrotemporal spike discharges on electroencephalogram: case report of a 10-year-old girl - Sun Young Seo; Su Jeong You (Korean Pediatric Society, 2016)
Coexistence of paroxysmal kinesigenic dyskinesia (PKD) with benign infantile convulsion (BIC) and centrotemporal spikes (CTS) is very rare. A 10-year-old girl presented with a 3-year history of frequent attacks of staggering while laughing and of suddenly collapsing while walking. Interictal electroencephalogram (EEG) revealed bilateral CTS, but no changes in EEG were observed during movement. The patient's medical history showed afebrile seizures 6 months after birth, while the family history showed that the patient's mother and relatives on the mother's side had similar dyskinesia. Genetic testing demonstrated that the patient had a heterozygous mutation, c.649_650insC, in the PRRT2 gene. To our knowledge, this constitutes only the second report of a patient with PKD, BIC, CTS, and a PRRT2 mutation.